2018
DOI: 10.3389/fimmu.2018.02384
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypogammaglobulinemia Can Be a Serious Condition

Abstract: Background: Most patients with primary antibody deficiency (PAD) suffer from less well-described and understood forms of hypogammaglobulinemia (unclassified primary antibody deficiency, unPAD). Because of the moderately decreased immunoglobulin levels compared to CVID, unPAD is generally considered to be clinically mild and not very relevant.Objective: To describe our cohort of—mainly—unPAD patients, and to analyze whether subgroups can be identified.Methods: Data were prospectively collected (February-2012 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Some studies have however shown impaired vaccine responses have correlated more closely with symptomatic state (31, 32). In one study, responses to tick-borne encephalitis vaccine was used as a neoantigen, responses which segregated with symptomatic state (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have however shown impaired vaccine responses have correlated more closely with symptomatic state (31, 32). In one study, responses to tick-borne encephalitis vaccine was used as a neoantigen, responses which segregated with symptomatic state (31).…”
Section: Discussionmentioning
confidence: 99%
“…These patients generally present themselves in secondary care, where the pre-test probability for severe antibody deficiency is inherently low. However, even milder hypogammaglobulinemia can lead to serious problems, requiring adequate medical attention (14). These milder patients are often not recognized due to lack of available test facilities in secondary care, and reluctance to refer many patients to an immunologist.…”
Section: Introductionmentioning
confidence: 99%
“…Once patients are identified with serum immunoglobulin G (IgG) below the normal limit, the need for immunoglobulin replacement can be established. However, the finding of low IgG concentration itself, without a clinical manifestation, is still a subject of discussion regarding the appropriate treatment (25). In our study, there was marked variability in IgG levels at the time of diagnosis, from 30 to 563 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin replacement is the basis of treatment for hypogammaglobulinemia, reducing sequelae from the respective immunological defect (4,25). The treatment can be administered intravenously or subcutaneously with variable doses, as determined by an individualized orientation.…”
Section: Discussionmentioning
confidence: 99%